Influence of boundary conditions on the response of multilayered plates with cohesive interfaces and delaminations using a homogenized approach (Fracture and Structural Integrity, 2014)
Stress and displacement fields in multilayered composites with interfacial imperfections, such as imperfect bonding of the layers or delaminations, or where the plies are separated by thin interlayers allowing relative motion, have large variations in the thickness, with characteristic zigzag patterns and jumps at the layer interfaces. These effects are well captured by a model recently formulated by the author for multilayered plateswith imperfect interfaces and affine interfacial traction laws (Massabò & Campi, Meccanica, 2014, in press; Compos Struct, 2014, 116, 311-324). The model defines a homogenized displacement field, which satisfies interfacial continuity, and uses a variational technique to derive equilibrium equations depending on only six generalized displacement functions, for any arbitrary numbers of layers and interfaces. The model accurately predicts stresses and displacements in simply supported, highly anisotropic, thick plates with continuous, sliding interfaces. In this paper the model is applied to wide plates with clamped edges and some  inconsistencies, which have been noted in the literature for models based on similar approaches and have limited their utilization, are explained. A generalized transverse shear force is introduced as the gross stress resultant which is directly related to the bending moment in the equilibrium equations of multilayered structures with imperfect interfaces and substitutes for the shear force of single-layer theory. An application to a delaminated wide plate highlights the potential and limitations of the proposed model for the solution of fracture mechanics problems.
Keywords: Cohesive interfaces